Uma proposta de aplicação do conteúdo de sequências e séries no Ensino Médio com auxílio do Geogebra - Fernando Henrique da Silva Vieira (2017)
In this work, we present the theory of sequences and numerical series from the analytical point of view. Using this theory, we present the method of exhaustion with applications such as quadrature of the parabola, approximation of the number π and the volume of the pyramid. In addition, we make suggestions of didactic proposals with the help of Geogebra to teachers of Mathematics who teach in High School